Africa's Development promises and prospects - Africa Progress Panel (Geneva Africa Progress Panel, 2008)
The objective of the report of the Africa Progress Panel is to examine the state of the continent in 2008, to focus world leaders' attention on delivering on existing commitments and to mobilise resources to deal with new challenges,in particular the crisis in food production. The panel has drawn on the work of various institutions and eminent individuals working on African issues to present an independent assessment of progress. We have strived to combine these assessments with our experience and judgment to highlight pressing concerns, inspire debate amongst leaders and civil society, and promote effective action
Keywords: Development, Climate Change Governance Food Crisis